What Effect Does CEO Power Has over Integrated Reporting? Evidence from Indonesian Listed Companies - Nurmala, Putri; Adiwibowo, Akhmad Sigit (Jurnal Dinamika Akuntansi dan Bisnis, 2024)
This study aims to analyze the role to chief executive officer (CEO) in integrated reporting (IR) adoption and whether growth opportunities moderate this role. This study is based on an unbalanced data panel of 106 firms listed on Indonesian Stock Exchange from 2017 to 2021 (530 observations). Using a panel regression model this study found that CEO power does not affect IR, and growth opportunities do not modify the relationship. Furthermore, this study also revealed that there is only one company sample that published IR based on the International Integrated Reporting Council (IIRC) framework in 2021. It is suggested that policy makers need to encourage IR adoption trough regulation and incentives.